Vogt–Koyanagi–Harada disease. (December 2012) - Attia, Sonia; Khochtali, Sana; Kahloun, Rim; Zaouali, Sonia; Khairallah, Moncef
Vogt–Koyanagi–Harada (VKH) disease is usually defined as a bilateral chronic granulomatous panuveitis that may be associated with CNS, auditory and integumentary manifestations. An autoimmune reaction against melanocyte antigens in genetically predisposed patients without history of ocular trauma is presumed to cause the disease. Features of ocular and extraocular involvement vary according to disease phase, and the condition can present with disease features limited to intraocular inflammation without associated systemic manifestations. Exudative retinal detachment is the most specific feature to acute VKH disease. Ancillary tests (mainly fluorescein angiography) may help in establishing the definitive diagnosis. On the other hand, sunset glow fundus is typical to chronic VKH disease. Complications are more likely to occur in the chronic recurrent phase. The mainstay of treatment for acute VKH relies on prompt systemic corticosteroid therapy initiated as a high dose and then tapered gradually. The duration of corticosteroid therapy is recommended to be at least 6 months. Other immunosuppressants may be given as second-line or, in selected cases, as first-line therapy. Early diagnosis with rapid initiation of corticosteroids reduces recurrence and thus improves visual prognosis.